Wednesday

April 23, 2014

April 23, 2014

Posted by **JT** on Tuesday, July 13, 2010 at 11:26am.

= 3m(m + 3)(m – 3)

its is not done? is this a cubeproblem?

- Algebra -
**PsyDAG**, Wednesday, July 14, 2010 at 4:27pm(m + 3)(m - 3) = m^2

**minus**9

**Related Questions**

Algebra - 3m^3 + 27m = 3m(m^2 + 9) = 3m(m + 3)(m – 3) I miss something? is this ...

Algebra - 3m^3 + 27m = 3m(m^2 + 9) = 3m(m + 3)(m – 3)

algebra - Posted this question and part of the answer was incorrect. a) 4L/3 = 6...

Man My Algebra must be annoying - 3m __ for m =20 and m = 1 5 __ 3 A. 3m = 320...

factoring - let f(m)=m^3 + 3m^2 + 3m + 1 notice f(-1) = 0, so m+1 is a factor. ...

pre algebra check - Find the product and simplify. m^2(3m^2) =3m^4????

algebra II - Adding Rational Expressions 1. 4m-2/3m+2 + 6m -4/ 3m+2=

algebra - Factor the polynomial completely 3m^2 -75 This is how I started to ...

PHYSICS - block 3M slides downward without friction. The string connecting ...

math - if 3M/2N=0.125, what is the value of N in terms of M? This is the workout...